An efficient two sample capture-recapture model with high recaptures - Danjuma Jibasen; Yusuf J. Adams (CBN Journal of Applied Statistics, 2013)
This paper proposed an efficient two sample capture-recapture model (Ma) with high recaptures and compared it with the existing models like the model of no factor effect (Mo), behavioral response model (Mb) and the Petersen model (Ms), using simulated data. We found that the Petersen model provides a better estimate of the population size when the observations follow a hypergeometric distribution and the population is overestimated when recapture n11 is high. It was also found that the proposed model provides a better estimator of the population size than the existing ones when the recapture is high. This model is particularly useful in situations where individuals respond positively to capture. This model can be applied to the estimation of the population of a locality and can be used to check inflated or disputed census figures effectively.
Keywords: C13; C15; C52; C63; 330; Captures-recapture; High recaptures; Fewer recaptures; Petersen model